2017
DOI: 10.1038/ncomms14245
|View full text |Cite
|
Sign up to set email alerts
|

Carbon translocation from a plant to an insect-pathogenic endophytic fungus

Abstract: Metarhizium robertsii is a common soil fungus that occupies a specialized ecological niche as an endophyte and an insect pathogen. Previously, we showed that the endophytic capability and insect pathogenicity of Metarhizium are coupled to provide an active method of insect-derived nitrogen transfer to a host plant via fungal mycelia. We speculated that in exchange for this insect-derived nitrogen, the plant would provide photosynthate to the fungus. By using 13CO2, we show the incorporation of 13C into photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 31 publications
0
74
1
2
Order By: Relevance
“…Growth promotion observed in plants colonized by entomopathogenic fungi might be attributed to the production of organic acids, phytohormones or siderophores, which can change the bioavailability of several nutrients . Furthermore, studies on endophytic fungus–plant interactions revealed that the positive effects on plant growth could also be due to fixation of nutrients . In our study, however, not all isolates had the same potential to provide these effects in the two different strawberry cultivars (‘Albion’ and ‘Pircinque’).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Growth promotion observed in plants colonized by entomopathogenic fungi might be attributed to the production of organic acids, phytohormones or siderophores, which can change the bioavailability of several nutrients . Furthermore, studies on endophytic fungus–plant interactions revealed that the positive effects on plant growth could also be due to fixation of nutrients . In our study, however, not all isolates had the same potential to provide these effects in the two different strawberry cultivars (‘Albion’ and ‘Pircinque’).…”
Section: Discussioncontrasting
confidence: 54%
“…[57][58][59] Furthermore, studies on endophytic fungus-plant interactions revealed that the positive effects on plant growth could also be due to fixation of nutrients. [60][61][62] In our study, however, not all isolates had the same potential to provide these effects in the two different strawberry cultivars ('Albion' and 'Pircinque'). Interestingly, the positive effects of fungal inoculations on biomass and fruit yield were observed mostly in the cultivar 'Albion', the cultivar presenting higher yield compared to the cultivar 'Pircinque'.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, plants can acquire N from soil insects through their endophytic associations with Metarhizium spp., which are ubiquitous soil-dwelling insect-pathogenic fungi (Behie, Zelisko, & Bidochka, 2012). Insect-derived N represented up to 48% of the plant N content, and this transfer process was driven by reciprocal allocation of C from the plant roots to the fungal mycelium (Behie et al, 2017). In addition, there is increasing evidence that dark septate endophytic (DSE) fungi have the potential to facilitate the transfer N to plants (Vergara et al, 2017).…”
Section: Pl Ants Acqu Ire Nitrog En By Recruiting Micro -Org Anis Mmentioning
confidence: 99%
“…The cosmopolitan fungus Metarhizium robertsii has versatile lifestyles; it is a pathogen of arthropods, a saprophyte and a colonizer of the rhizosphere and plant root (Roberts and St. Leger, ; Behie et al ., ; Guo et al ., ). A multiyear field trial revealed that the ability of M. robertsii to maintain large populations is determined by its tolerance to abiotic stresses including temperature fluctuation and UV radiation (Fang and St. Leger, ; Wang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…A multiyear field trial revealed that the ability of M. robertsii to maintain large populations is determined by its tolerance to abiotic stresses including temperature fluctuation and UV radiation (Fang and St. Leger, 2010;Wang et al, 2011). Metarhizium robertsii is becoming a model for studying intimate association with different plant and insect species and assessing fungal evolution in natural communities (Behie et al, 2017;Zhang et al, 2017). Cross protection in M. robertsii may involve accumulation of trehalose and mannitol and up-regulation of HSPs (Rangel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%